Combining transcranial direct current stimulation with group cognitive behavioral therapy developed to treat rumination: a clinical pilot study - Horczak, Paula; Wang, Chanyu; De Witte, Sara; De Smet, Stefanie; Remue, Jonathan; De Raedt, Rudi; Vanderhasselt, Marie-Anne; Wu, Guo-Rong; Lemmens, Gilbert M. D.; Baeken, Chris (Frontiers in Neurology, 2023)
Background As part of repetitive negative thinking (RNT), rumination is a maladaptive cognitive response style to stress or negative mood which can increase the risk of depression and may prohibit complete recovery. Cognitive behavioral therapy (CBT) and transcranial direct current stimulation (tDCS) both proved to be effective in decreasing rumination. However, the combined effects of tDCS and CBT interventions on rumination have not yet been explored. The first aim of this pilot study is to investigate whether the combination of tDCS and CBT has an accumulating positive effect on modulating state rumination. The second aim is to assess the feasibility and safety profile of the proposed combined approach. Method Seventeen adults aged 32–60 years, suffering from RNT, were referred by their primary care professional to participate in an 8-week group intervention for RNT (“Drop It”) comprising 8 sessions of CBT. Before each CBT session, patients underwent one double-blinded prefrontal active (2 mA for 20 min) or sham tDCS (anode over F3, cathode over the right supraorbital region) combined with an internal cognitive attention task focused on individual RNT, i.e., online tDCS priming. During each session, the Brief State Rumination Inventory was used to assess state rumination. Results A mixed effects model analysis revealed no significant differences between the stimulation conditions, weekly sessions, or their interaction in terms of state rumination scores. Conclusion Overall, the combination of online tDCS priming followed by group CBT was found to be safe and feasible. On the other hand, no significant additional effects of this combined approach on state rumination were established. Although our pilot study may have been too small to find significant clinical effects, future larger RCT studies on combined tDCS-CBT treatment protocols may reevaluate the selection of internal cognitive attention tasks and more objective neurophysiological measurements, consider the optimal timing of the combination (concurrently or sequentially), or may add additional tDCS sessions when following CBT.